Pengaruh Leverage, UkuranPerusahan, Kualitas Audit dan Independensi Auditor Terhadap Manajemen Laba Pada Perusahaan Manufaktur Yang Terdaftar di BEI Periode 2015-2017. - Rosmiati -; Jihen Ginting (JAKPI - Jurnal Akuntansi, Keuangan & Perpajakan Indonesia, 2019)
Abstrak : The problem in this study is how the influence of leverage, company size, audit quality and auditor independence on earnings management. The purpose of this study was to determine the effect of leverage, firm size, audit quality and auditor independence on earnings management. The population in this study are the entire companies of manufacturing companies listed on the Indonesia Stock Exchange in 2015-2017, which amounted to 143. However, from this population there are 128 annual reports that do not meet the research criteria and which are 15 annual reports in each year due to this study took 3 years of data, the number of samples was 45 annual reports. The analysis technique uses a purposive sampling technique with several criteria. The analysis technique in this study used multiple regression analysis with the help of the SPSS program. The results of this study indicate that Leverage, Company Size, Audit Quality and Auditor Independence simultaneously have no effect on earnings management. Partially Leverage has a negative effect on earnings management, Company Size does not affect earnings management, Audit Quality does not affect earnings management and Auditor Independence does not have an effect on earnings management. Keywords: Leverage, Company Size, Audit Quality, Auditor Independence, Earnings Management.